The Leech's Politeness Principle in the Dialogues of the Short Film 'Ibu' on the Bakar Production YouTube Channel - Miftoqul Khasanah; Budhi Setiawan; Kenfitria Diah Wijayanti (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2024)
The implementation of politeness principles can still be found in a film, one of which is the short film "Ibu" on the YouTube channel Bakar Production. Adhering to these politeness principles can serve as an example for viewers of the film. Therefore, this study aims to describe and explain the politeness principles (maxim of wisdom, maxim of generosity, maxim of praise, maxim of humility, maxim of agreement, and maxim of sympathy) according to Leech in the short film "Ibu" on the YouTube channel Bakar Production to prevent inappropriate speech in communication. The method used in this study is qualitative descriptive with a pragmatic approach. The data collection technique used in this study is document analysis. The data analysis technique used in this study is flow analysis. The data validation technique used for this research is theory triangulation. The results of this study reveal the presence of 29 instances of adherence to Leech's politeness principles, encompassing all six maxims. By adhering to Leech's politeness principles in the film, it is hoped that society, especially teenagers, can emulate polite language in the film and apply it in their daily communication.